Negotiating Difference: How Aboriginal Athletes in the Maritimes Brokered their Involvement in Canadian Sport. Issue 16 (1st November 2016) - Forsyth, Janice; Lodge-Gagné, Vanessa; Giles, Audrey
Abstract: Aboriginal perspectives on experiences in sport in Canada are largely missing from the existing body of literature on sociocultural aspects of sport, but this is especially the case in terms of Aboriginal people from the Maritimes region of Canada. Such an absence impedes our understanding of sport as an important cultural institution that can be used to normalize certain social practices, as well as challenge them. In this paper, we aim to contribute to the body of knowledge on Aboriginal sport by examining the lived experiences of nine elite Aboriginal athletes from the Maritimes, specifically those who won a Tom Longboat Award, through a postcolonial lens. In doing so, we reveal some of the nuanced power relationships that shaped their involvement in organized, competitive sport – distinctions that are not often addressed in the scholarly literature and thus limit our understanding of the complex and sometimes difficult realities of Aboriginal sport development in Canada. The participants' stories tell us a great deal about the recipients as individuals, about Aboriginal peoples' involvement in contemporary sport, and how the ways in which they negotiated difference within sport marked their lives.